Precision-Guided or Blunt? The Effects of US Economic Sanctions on Human Rights - Jerg Gutmann; Matthias Neuenkirch; Florian Neumeier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
This study contributes to the literature that analyzes the consequences of economic sanctions for the target country's human rights situation. We offer a political economy explanation for different types of human rights infringements or improvements in reaction to economic shocks caused by sanctions. Based on this, we derive hypotheses linking sanctions to four types of human rights: economic rights, political and civil rights, basic human rights, and emancipatory rights. We use endogenous treatment regression models to estimate the causal average treatment effect of US economic sanctions on each type of human rights within a uniform empirical framework. In contrast to previous studies, we find no adverse effects of sanctions on economic rights, political and civil rights, and basic human rights, once the endogenous selection into sanctions is modelled. With respect to women's rights, our findings even indicate a positive relationship. Emancipatory rights are, on average, strengthened when a country experiences sanctions by the US. Our findings are robust and we find little evidence for effect heterogeneity between types of target countries or sanctions. Most importantly, this study shows that the endogeneity of treatment assignment must be modelled when the consequences of sanctions are studied empirically.
Keywords: F51; F52; F53; K10; K11; P14; P16; P26; 330; Democratization; discrimination; economic sanctions; endogenous treatment model; human rights; repression; United States